Handbook on the Consequences of Sentencing and Punishment Decisions - Huebner, Beth M.; Frost, Natasha A.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Handbook on the Consequences of Sentencing and Punishment Decisions, the third volume in the Routledge ASC Division on Corrections & Sentencing Series, includes contemporary essays on the consequences of punishment during an era of mass incarceration. The Handbook Series offers state-of-the-art volumes on seminal and topical issues that span the fields of sentencing and corrections. In that spirit, the editors gathered contributions that summarize what is known in each topical area and also identify emerging theoretical, empirical, and policy work. The book is grounded in the current knowledge about the specific topics, but also includes new, synthesizingmaterial that reflects the knowledge of the leading minds in the field.Following an editors introduction, the volume is divided into four sections. First, two contributions situate and contextualize the volume by providing insight into the growth of mass punishment over the past three decades and an overview of the broad consequences of punishment decisions. The overviews are then followed by a section exploring the broader societal impacts of punishment on housing, employment, family relationships, and health and well-being. The third section centers on special populations and examines the unique effects of punishment for juveniles, immigrants, and individuals convicted of sexual or drug-related offenses. The fourth section focuses on institutional implications with contributions on jails, community corrections, and institutional corrections.
INTRODUCTION -- The Consequences of Sentencing and Punishment Decisions--Beth M. Huebner and Natasha A. Frost -- I. CONSEQUENCES OF PUNISHMENT DECISIONS -- 1.Historical Trends in Punishment and the Lens of American Federalism--Michael C. Campbell and Paige E. Vaughn -- 2.Collateral Sanctions: The Intended Collateral Consequences of Felony Convictions--Tanya N. Whittle -- II.BROAD IMPACTS -- 3. The Collateral Consequences of Incarceration for Housing--David S. Kirk -- 4.Residential Insecurities and Neighborhood Quality Following Incarceration--Brianna Remster and Cody Warner -- 5.Impact of Incarceration on Employment Prospects--Robert Apel and Anke Ramakers -- 6.Incarceration, Reentry, and Health--Chantal Fahmy and Danielle Wallace -- 7.The Psychological Effects of Contact with the Criminal Justice System--Thomas P. LeBel and Matt Richie -- 8.Impacts of Incarceration on Children and Families--Miriam Northcutt Bohmert and Sara Wakefield -- 9.Impacts of Conviction and Imprisonment for Women--Miriam Northcutt Bohmert, Matthew Galasso, and Jennifer Cobbina -- III. CONSEQUENCES OF SENTENCING DECISIONS -- 10.Punished for being Punished: Collateral Consequences of a Drug Offense Conviction--Ashley Nellis -- 11.Compounded Stigmatization: Collateral Consequences of a Sex Offense Conviction--Kimberly R. Kras, Morgan McGuirk, Breanne Pleggenkuhle, and Beth M. Huebner -- 12.The Hidden Consequences of Visible Juvenile Records--Megan C. Kurlychek and Riya Saha Shah -- 13.Deportation as a Collateral Consequence--Carlos E. Monteiro -- IV. INSTITUTIONAL CONTEXTS----14.Mass Jail Incarceration and Its Consequences--Joshua C. Cochran and Elisa L. Toman -- 15.Collateral Consequences of Pretrial Detention--Natalie Goulette and John Wooldredge -- 16.The Impact of Restrictive Housing on Inmate Behavior: A Systematic Review of the Evidence--Ryan M. Labrecque and Paula Smith -- 17.The Impacts of Privatization in Corrections: The State of Evidence and Recommendations for Moving Forward--Andrea Montes Lindsey and Daniel P. Mears -- V.BROAD IMPLICATIONS----18.Raise the Age Legislation as a Prevention Approach to Address Mass Incarceration--Danielle Tolson Cooper and Jennifer L. Klein -- 19.Mass Incarceration in Jail and Family Visitation--Emma Conner -- 20.The Hardest Time: Gang Members in Total Institutions--David C. Pyrooz and Meghan M. Mitchell -- 21.Exportation Hypothesis: Bringing Prison Violence Home to the Community--Don Hummer and Eileen M. Ahlin
Includes bibliographical references and index.
Also available in print format.
Keywords: Punishment -- United States; Sentences (Criminal procedure) -- United States; Criminal justice, Administration of -- United States; Electronic books